Day of the week to tweet: a randomised controlled trial. Issue 4 (4th April 2019) - Jayaram, Mahesh; Adams, Clive E; Friedel, Johannes S; McClenaghan, Eimear; Montgomery, Alan A; Välimäki, Maritta; Schmidt, Lena; Xia, Jun; Zhao, Sai
Abstract : Objective: To assess the effects of using health social media on different days of the working week on web activity. Design: Individually randomised controlled parallel group superiority trial. Setting: Twitter and Weibo. Participants: 194 Cochrane Schizophrenia Group full reviews with an abstract and plain language summary web page. There were no human participants. Interventions: Three randomly ordered slightly different messages (maximum of 140 characters), each containing a short URL to the freely accessible summary page, were sent on specific times on a single day. Each of these messages sent on Tuesday, Wednesday, Thursday and Friday was compared with the one sent on Monday. Outcome: The primary outcome was visits to the relevant Cochrane summary web page at 1 week. Secondary outcomes were other metrics of web activity at 1 week. Results: There was no evidence that disseminating microblogs on different days of the working week resulted in any differences in target website activity as measured by Google Analytics (n=194, all page views, adjusted ratios of geometric means 0.86 (95% CI 0.63 to 1.18), 0.88 (95% CI 0.64 to 1.21), 0.88 (95% CI 0.65 to 1.21), 0.91 (95% CI 0.66 to 1.24) for Tuesday–Friday, respectively, overall p=0.89). There were consistent findings for all outcomes. However, activity on the review site substantially increased compared with weeks preceding the intervention. Conclusion: There are no clear differences in the effect when 1 weekday is compared with another, but our study suggests that using microblogging social media such as Twitter and Weibo do increase information-seeking behaviour on health. Tweet any day but do Tweet.